Peritonitis secondary to infected urachal sinus with complicated umbilical hernia - S., Ravi; R. I., Divya (International Surgery Journal, 2022)
An umbilical hernia is a protrusion of an intra-abdominal organ fully or part of it from an umbilical opening. Umbilical hernia is a common problem encountered in surgical out-patient departments. The urachus is an embryonic tube that connects the upper portion of the bladder to the umbilicus. The urachal canal normally obliterates and forms the median umbilical ligament. When this process fails, four different embryological abnormalities can result: urachal sinus, patent urachus, urachal cyst, vesicourachal diverticulum. The association of urachal sinus and hernia is rare. We present one such case of a 49 year old patient with peritonitis secondary to infected urachal sinus with complicated umbilical hernia.